Does Patient Counselling Correspond to Medication Adherence in Chronic Diseases? - A Scoping Review - Rojina Basnet; Rajan Bhandari; Sabyata Gautam; Nishant Lama; Shreejana KC; Tulsi Ram Bhandari (Journal of Karnali Academy of Health Sciences, 2021)
Background: Quality care is essential to minimize the complication or consequences of chronic diseases. The main objective of this scoping review was to identify the role of patient counseling on medication adherence in chronic diseases.